SAT0429 The OA TRIAL Bank: Meta-Analysis of Individual Patient Data Show That Patients with Severe Pain or with Inflammatory Signs Detected by Ultrasound Especially Benefit from Intra-Articular Glucocorticoids for Knee or Hip Oa. (10th June 2014) - Van Middelkoop, M.; Arden, N.; Atchia, I.; Birrell, F.; Chao, J.; Lambert, R.; Ravaud, P.; Bijlsma, J.W.; Doherty, M.; Dziedzic, K.; Lohmander, S.; McAlindon, T.; et al.
Abstract : Background: Based on small to moderate effect sizes for the wide range of symptomatic treatments in osteoarthritis (OA) and on the heterogeneity of OA patients, treatment guidelines for OA have stressed the need for research on clinical predictors of response to treatment. Objectives: To evaluate the efficacy of intra-articular (IA) glucocorticoids for knee and hip OA for subgroups of patients with severe pain, and inflammation on short term follow-up using IPD from existing trials. Methods: Randomized trials evaluating one or more IA glucocorticoid preparation in patients with knee or hip OA, published from 1995 up to June 2012 were selected from the existing literature. The presented preliminary analyses include the comparison between IA glucocorticoids and placebo, since data included in this comparison are complete. Individual data obtained from original trials included patient characteristics, disease characteristics and outcomes measured. All analyses were performed following our published protocol.(1) The primary outcome was pain severity at short-term follow-up (up to 4 weeks). The subgroup factors assessed included severe pain and signs of inflammation. A multilevel regression analysis was applied to calculate the interaction effects. Analyses were adjusted for baseline pain severity, age, gender and BMI. Results: Seven published randomized clinical trials including 309 patients were included.(additional data of 360 patients affirmed). Of these, four studies (n=225) compared glucocorticoids with placebo. A significant positive interaction was found between severe pain at baseline and treatment effect (interaction coefficient 13.6, 95%CI 1.4-25.8). A non-significant overall interaction estimate was found for inflammatory signs 12.5 (95%CI -7.22-32.3). However, a strongly positive interaction estimate (45.3, 95%CI 24.4-66.1) was found for inflammation and treatment effect when analyzed in the studies where inflammation was measured by ultrasound. Conclusions: Patients with severe pain at baseline do benefit significantly more from IA glucocorticoid injections than those with less severe pain. However inflammation defined by ultrasound provided an even more significant measure of a positive treatment response of IA glucocorticoids in patients with knee or hip OA. The differences in treatment response at short-term follow-up between IA glucocorticoid treatment and IA placebo were much larger when inflammatory signs, measured by ultrasound, were present compared to absence of inflammatory signs. References: van Middelkoop M, Dziedzic KS, Doherty M, et al. Individual patient data meta-analysis of trials investigating the effectiveness of intra-articular glucocorticoid injections in patients with knee or hip osteoarthritis: an OA Trial Bank protocol for a systematic review. Syst Rev. 2013;2:54. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2250